2019
DOI: 10.2136/vzj2019.03.0027
|View full text |Cite
|
Sign up to set email alerts
|

Bound Water, Phase Configuration, and Dielectric Damping Effects on TDR‐Measured Apparent Permittivity

Abstract: Core Ideas Frequency‐dependent bound water permittivity influences TDR‐measured Ka. Predictive power of frequency‐independent dielectric mixing models is limited. TDR measurements of Ka should be paired with effective frequency measurements. The time domain reflectometry (TDR) method measures the soil apparent permittivity (Ka), which is the basis for estimation of soil volumetric water content (θ) via an empirical calibration equation or dielectric mixing model. The relationship between Ka and θ [i.e., Ka(θ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…(1.3%) and could be calibrated to a lower level (1%) for a specific soil type. However, this equation was found to be restricted to unfrozen soils and soils with low specific surface areas (Dirksen and Dasberg, 1993;Dobson et al, 1985;Dyck et al, 2019). A special calibration was required for partially frozen soil (Stein and Kane, 1983).…”
Section: Soil Water Content Measurement With Traditional Tdr Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1.3%) and could be calibrated to a lower level (1%) for a specific soil type. However, this equation was found to be restricted to unfrozen soils and soils with low specific surface areas (Dirksen and Dasberg, 1993;Dobson et al, 1985;Dyck et al, 2019). A special calibration was required for partially frozen soil (Stein and Kane, 1983).…”
Section: Soil Water Content Measurement With Traditional Tdr Methodsmentioning
confidence: 99%
“…This discovery significantly boosted the applications of TDR in soil science and opened a new era for soil water measurements. Many subsequent investigations, including TDR cable testers, TDR probe designs (Zegelin et al, 1989), TDR waveform recording or analysis tools (Wang et al, 2016), and TDR calibration curves (Dirksen and Dasberg, 1993;Dyck et al, 2019;Friedman, 1998;He and Dyck, 2013;He et al, 2016;Malicki et al, 1996;Ponizovsky et al, 1999;Robinson et al, 2005a;Roth et al, 1990) led to improvements in TDR capabilities. Detailed history of TDR developments in soil science studies is reported by Topp et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Soils are well known to contain “bound” water, often estimated as the amount of hygroscopic water [ 14 ], though to what extent this impacts dielectric measurements remains poorly understood and open to investigation [ 15 , 16 , 17 , 18 , 19 , 20 ]. The impact of “bound” water on dielectric measurements has support based on experimental evidence mostly from work conducted on mineral and non-mineral surfaces, e.g., in food [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric permittivity is sensitive to changes in temperature (Seyfried & Grant 2007). In some soils, as it does in the water, the molecular vibrations increases with the temperature and, these vibrations, with the presence of an electric field applied; hinder the rotational dipole moment (Dyck et al 2019, Mohamed & Paleologos 2018. In practical terms, the dielectric permittivity decreases as the temperature increases.…”
Section: Discussionmentioning
confidence: 99%